Pharmacognostic evaluation of leaf and root bark of Holoptelea integrifolia Roxb. - Kumar, Dinesh (Asian Pacific Tropical Medicine Press, 2012)
OBJECTIVE: To evaluate the pharmacognostic characters of an important medicinal plant, Holoptelea integrifolia (H. integrifolia) Roxb. METHODS: The pharmacognostic studies were carried out in terms of organoleptic, microscopic, macroscopic and fluorescence analysis. RESULTS: The characteristic microscopic features of leaves were observed as trichomes, multicellular trichomes, xylem cells, phloem cells, collenchyma, vascular bundles, spongy parenchyma and palisade cells. The characteristic microscopic features of root bark included cork cambium, primary cortex, phloem fibers, medullary rays, endodermis, pericycle and lignified fibers in the transverse section and longitudinal section. The characteristic microscopy of root bark powder showed the presence of cortex cells, sieve tubes, calcium oxalate crystals and lignified fibers. Macroscopic study showed that leaf shape-oval, apex-acute, base-cordate and leaf margin was entire with glabrous surface, bitter taste and characteristic odour. The morphological features of root bark showed deep fissured, rough and firm surface with rhitydome and the periderm parallel to cambium. CONCLUSIONS: Various pharmacognostic characters observed in this study help in the identification and standardization of H. integrifolia.